Application of aerosys software to calibration of digital camera Canon EOS 300D - Kwoczyńska, B. (Видавництво Національного університету "Львівська політехніка", 2007)
This publication demonstrates the possibility of use of free AeroSys Consulting software to calibration of digital cameras. Investigations were carried out with digital camera Canon EOS 300D. Before the elements of internal orientation of camera were determined, the stability of CMOS matrix registration of images was checked out. Appropriate pictures were taken to measure coordinates of checkpoi nts by AutoCAD 2000. Parameters of camera cal i brati on were determi ned with the modul es Direct Linear Transformation and Camera Calibration program AeroSys.